EFEKTIVITAS BIMBINGAN KELOMPOK UNTUK MENINGKATKAN EFIKASI DIRI SISWA DI SANGGAR BIMBINGAN KEPONG - Tusadiah, Halimah; M Fauzi Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this study is to determine whether the Kepong Guidance Center's group counseling sessions were successful in improving the self-efficacy of third-grade elementary school children. A person's self-efficacy can be defined as their confidence in their own ability to complete tasks or face challenging situations. Using a one-group pretest-posttest quasi-experimental design, this study employed quantitative methods. The research population consisted of ten third-grade students, aged between eight and nine years old, who participated in the Kepong Guidance Center’s counseling group during the 2024–2025 academic year. A saturated sampling method, or total population sampling, was used in the sampling process. The research instrument was adapted to suit the specific characteristics of elementary school students and utilized a validated self-efficacy scale. For this study, a paired sample t-test was used to compare the participants' levels of self-efficacy before and after participating in the support group. According to the data, students’ self-efficacy significantly increased after attending the counseling group (t-value = 8.456; p < 0.05). The average self-efficacy score increased substantially, from a low of 45.2 to a high of 68.8. These results suggest that elementary school students can benefit from group counseling as an alternative intervention to traditional counseling and guidance programs, as group counseling has proven effective in enhancing students' self-efficacy.